Information Seeking Behaviours of Primary School Students on the Internet - Selda Ekici; Nazan Özenç Uçak (Türk Kütüphaneciliği)
The aim of this study is to determine the primary school students ’ attitudes about the Internet, usage patterns, information seeking behaviours on the Internet and referencing patterns. Eight grade students from two schools, including one of the state and one of the private, were selected to achieve the objective of the study. A questionnaire was conducted to total of 149 students. With this study tried to determine the following characteristics of students: Using computer and Internet skills, intended uses of the Internet, information needs and information seeking behaviour, problems encountered in accessing information, how do they evaluate the information, how to use assignment and awareness of the referencing. The result shows that primary school students refer the Internet first for access to the information. They also perceive Internet as up-to-date, easily accessible and as an ambience where one can find all kinds of information; but they don’t believe the necessity to cite the print or internet sources where they obtain the information they use in their homeworks.